Data Security Analysis with Triple DES Cryptographic Algorithm - Sipayung, Liskedame Yanti; Purba, Megaria (Institute of Computer Science (IOCS), 2023)
The Data Encryption Standard (DES) is the first and most significant modern symmetry encryption algorithm. DES was released by the United States' National Bureau of Standards in January 1977 as an algorithm used for unclassified data (information that has nothing to do with national security). Although DES has been widely used in many applications around the world, there are still many controversial issues regarding the security of this algorithm. Therefore, this paper aims to discuss the security analysis of the DES cryptographic algorithm and also the security analysis of the DES algorithm variations, namely Double DES and Triple DES. Because the level of secrecy of the 3DES algorithm lies in the length of the key used, the use of the 3DES algorithm is considered more secure than the DES algorithm. To facilitate the use of the 3DES algorithm, a 3DES algorithm program was created with computer software tools, namely Matlab 7.0.4 which can encrypt and decrypt files with the .txt extension.